Ecoviolence studies human exploitation and environmental crime - Stoett, Peter 1965-; Omrow, Delon Alain (Cambridge University Press, 2025)
Ecoviolence, defined broadly as the intersection between human-human exploitation and the destruction of nature, is one of the defining features of our time. This book collects ten case studies examining the intersection between the exploitation of human beings and environmental harm. Topics discussed include the wildlife trade, ecoviolence at sea, natural resource exploitation in Latin America and Africa, human trafficking induced by extreme weather events, climate change-related language death, and the confluence of drug cartels and environmental destruction. The book argues that Ecoviolence Studies has emerged as an expanded, multidisciplinary field in its own right, and that policy responses and the search for environmental and social justice should reflect accumulated knowledge in this area. It is an insightful volume for researchers and graduate students working in green criminology, Earth system governance, environmental politics, human rights, environmental and international law, and related areas
Title from publisher's bibliographic system (viewed on 14 Feb 2025)
Ecoviolence studies and human security / Peter Stoett and Delon Alain Omrow -- The links between human trafficking and wildlife trafficking / Michelle Anagnostou and Daan van Uhm -- Preventing a secondary disaster : how emergency management agencies can prepare and respond to disaster linked exploitation / Benjamin Greer -- Ecoviolence at sea / Matilda Petersson and Sofia Käll -- There will be blood : the return of the frontier logic in Guyana and hyper-exploitation in the mining sector / Delon Alain Omrow -- Artisanal gold mining in Uganda ; towards formalisation as remediation of dignity and rights / Julius Kaka -- Searching for shelter in the climate crisis era : ecocide and migration / Ascensión García Ruiz -- Climate change, violence, and ecocide / Rob White -- Sea of Cortez : crime and ecosystem crossroads / Francisco Cuamea and Delon Alain Omrow -- Minority languages as collateral damage in the climate crisis-the incidental result of ecoviolence on Y Gymraeg/Welsh Language
Keywords: Offenses against the environment / Law and legislation; Environmental law, International / Political aspects; Environmental ethics